COMPORTAMENTO DE GENÓTIPOS DE FEIJOEIRO AO ATAQUE DE BEMISIA TABACI (GENN.) BIÓTIPO B (HEMIPTERA: ALEYRODIDAE) - Jesus, F.g.; Martins, B.c.; Rocha, F.s.; Boiça, A.l. [UNESP]; Carbonel, S.a.m.; Chiorato, A.f. (Instituto Biológico, 2021)
Bean genotypes were evaluated under the infestation of Bemisia tabaci (Genn.) biotype B under field conditions in the dry and rainy season. The genotypes used were IAC-Tybatã, IAC-Una, FT-Nobre, Pérola, LP 98-122, LP 02-130, LP 01-38, LP 9979, BRSPontal, BRS-Requinte, BRS-Triunfo, BRS-Grafite, CV-48 and Z-28. The experiment was arranged in randomized blocks with 14 treatments and 3 replications. The evaluations were made on a weekly basis by counting B. tabaci biotype B eggs and nymphs on 10 leaflets per plot. In the dry season the least oviposited genotypes by B. tabaci biotype B were IAC-Una and LP 02-130, while the most oviposited were Z-28 and Pérola. The least presence of nymphs of whitefly was observed on LP 98-122 and FT-Nobre, and the most on LP 01-38, Perola and Z-28. For the rainy season the genotypes did not differ in relation to the attack of B. tabaci biotype B. The yield factors presented a statistical difference only in the dry season.

Avaliou-se o comportamento de genótipos de feijoeiro sob infestação de Bemisia tabaci (Genn.) biótipo B em condições de campo, nas épocas de cultivo “da seca” e “das águas”. Utilizaram-se os genótipos IAC-Tybatã, IAC-Una, FT-Nobre, Pérola, LP 98-122, LP 02-130, LP 01-38, LP 9979, BRS-Pontal, BRS-Requinte, BRS-Triunfo, BRS-Grafite, CV-48 e Z-28. Adotou-se o delineamento de blocos casualizados com 14 tratamentos e três repetições. As avaliações foram realizadas semanalmente, contando-se o número de ovos e de ninfas de B. tabaci biótipo B em dez folíolos por parcela. Na safra “da seca” os genótipos menos ovipositados por B. tabaci biótipo B foram IAC-Una e LP 02-130 e os mais ovipositados foram os genótipos Z-28 e Pérola. As menores presenças de ninfas de mosca-branca foram observadas em LP 98-122 e FT-Nobre e as maiores em LP 01-38, Pérola e Z-28. Para a safra “das águas” os genótipos não diferiram entre si em relação ao ataque de B. tabaci biótipo B. Os fatores da produção apresentaram diferença estatística somente na safra das secas.
BEHAVIOR OF BEAN GENOTYPES TO ATTACK BY BEMISIA TABACI (GENN.) BIOTYPE B (HEMIPTERA: ALEYRODIDAE).
Keywords: Phaseolus vulgaris; whitefly; host plant resistance; Phaseolus vulgaris; mosca-branca; resistência de plantas a insetos